Teachers' Pedagogical Adaptation to Digital Culture: Qualitative Insights from Technology-Mediated Language Teaching - Ahmad Lizamuddin; Mohammad Noor Zuhri; Muhammad Jauhari Sofi (UIN Raden Mas Said Surakarta, Indonesia, 2025)
The rapid expansion of digital culture has reshaped the pedagogical landscape of language teaching, requiring teachers to rethink their instructional practices within technology-mediated environments. This study aims to explore how secondary school language teachers adapt their pedagogical approaches to the demands of digital culture and what factors influence their adaptation processes. Using a qualitative descriptive design, data were collected from ten language teachers in Kendal Regency through open-ended questionnaires and analyzed thematically. The findings reveal that pedagogical adaptation is a multidimensional process characterized by shifts from teacher-centered to student-centered digital orientations, the development of context-responsive digital strategies, and the negotiation of sociotechnical challenges such as device inequality, unstable internet, and diminished authentic interaction in online settings. The results also show that teacher professional identity and reflective decision-making function as central mechanisms shaping the depth and direction of pedagogical adaptation. This study extends existing theoretical frameworks-including TPACK, adaptive expertise, teacher identity, and pedagogical reasoning-by demonstrating how they interact dynamically within digital language teaching contexts. Practically, the study underscores the need for professional development that emphasizes reflective digital pedagogy, institutional support for technological equity, and collaborative spaces for sharing adaptive practices. The findings highlight that effective digital language teaching emerges not merely from tool proficiency but from contextually informed instructional reasoning and identity-driven pedagogical transformation.